A step forward in elucidating the mystery of OCD - Kohl, Sina Maya; Sartorius, Alexander (European archives of psychiatry and clinical neuroscience, 2015)
Obsessive-compulsive disorder represents one of the most disabling psychiatric disorders. The underlying pathophysiology is not fully understood. In a recent Science article, Ahmari and colleagues enlighten fundamental aspects of obsessive-compulsive disorder by means of optogenetic stimulation, thereby also elucidating the usefulness of SSRI in the treatment for OCD.